Beyond a deficit model of strengths training in schools: Teaching targeted strength use to gifted students. (May 2017) - Bates-Krakoff, Justine; McGrath, Robert E; Graves, Karen; Ochs, Lynn
Prior literature on the use of character strengths suggests that both deficiencies and excesses in the use of strengths can be problematic. While most school-based training in character strengths tends to focus on the former issue, an example is provided of a school-based program offered by the Mayerson Academy in partnership with the VIA Institute on Character that does not focus on deficiency but rather celebrates enhancing one's own personal key strengths. This program, entitled Thriving Learning Communities, will be implemented in 42 Cincinnati public schools this year. It aims to motivate students, as well as educators, to perform at their highest levels through encouraging increased use of character strengths. We provide an overview of the program and discuss how it may be modified by the teacher to offer a more nuanced perspective on character strengths within a gifted student population. Specifically, within a gifted classroom setting, we discuss ways in which educators can encourage gifted students to understand the importance of balancing their strengths and effectively matching their use of strengths to the situation. In addition to focusing on the use of signature or top strengths, we suggest a program that would aid gifted students in deciphering when it is most and least appropriate to use top strengths, through a dial-up/dial-down framework for targeted strength use.